المستودعات الرقمية في دعم البحث العلمي بالجزائر 2020/2021 - طاهرة, عمورية; بلخوجة, خولة (كلية العلوم الاجتماعية, 2021)
e image of the information society has changed with the development of e means of communication and the emergence of the Internet, so the ormation flows and changes at a tremendous speed, prompting scientists to d a solution to circulate and share scientific knowledge at a speed mparable to the speed of its change, so they invented the institutional digital positories that scientists wanted a solution for disseminating information and owledge without restrictions on the line. “A topic that did not receive its are of the research despite its importance. Therefore, in this study we dealt h analyzing the role of digital repositories in achieving scientific research d information retrieval. We applied an analytical and descriptive approach to em, and through it we reached conclusions on the topic, the most important which is that the digital collections within university libraries are mostly emoranda and theses allow, and lack the scientific content that is the ckbone of scientific research, such as scientific articles, laboratory research, nference papers, and scientific journals, as well as the bibliographic cards of exes that do not allow access to the full text of the document, which deviate m the path of university repositories from its primary goal And to become y a bibliographic guide, as it uses the open source Dspace software, and it ks the minimum services, and does not adopt a specific publishing policy, d if it exists, it is not announced, does not work with data exchange otocols, and most of it is not registered via global repository directories.
Keywords: المستودعات الرقمية-البحث العلمي-دعم البحث العلمي بالجزائر